An update on cardiovascular effects of obstructive sleep apnoea syndrome. Issue 1091 (17th June 2016) - Uyar, Meral; Davutoglu, Vedat
Abstract: Obstructive sleep apnoea syndrome is an important health problem which may cause or worsen systemic diseases. Chronic intermittent hypoxia during repetitive airflow cessations may cause endothelial dysfunction. Sleep apnoea is also shown to be associated with hypercoagulability which may be due to decreased nitric oxide levels and impaired vasodilatation. Endothelial dysfunction, increased systemic inflammation, sympathetic nervous system activation, increased oxidative stress and dysglycaemia may all contribute to cardiovascular processes such as hypertension, arrhythmia, stroke, heart failure and coronary artery disease in patients with obstructive sleep apnoea. Treatment approaches in patients with obstructive sleep apnoea mainly focus on maintaining upper airway patency either with positive airway pressure devices or upper airway appliances. Strategies involving positive airway pressure therapy are associated with decreased morbidity and mortality. Obstructive sleep apnoea should be suspected as an underlying mechanism in patients with cardiovascular disease and warrants appropriate treatment.